1992
DOI: 10.1002/maco.19920431002
|View full text |Cite
|
Sign up to set email alerts
|

Autoklaven‐Untersuchungen der Spannungsrißkorrosion von Fe‐Cr‐Ni‐Legierungen in NaCl/Co2/H2S‐Medien

Abstract: Bei der Erdol-und Erdgasgewinnung nehmen mit zunehmendcr Tiefe der Lagerstatte die korrosiven Bedingungen zu. Als Medien liegen chloridreiche WBsser und Gasgemische mit HZS und COz bei hohcn Driicken und Temperatiiren vor. Dic hicr einsetzbaren Werkstoffe sind hoherfeste hochlegierte Stahle uiid Nickelbasis-Legierungen. Fur einen sicheren Betrieb mussen die Korrosionseigenschaftcn gcpruft sein. Die Medien enthalten H2S und Chlorid-Ionen, die bcide als kritische Komponenten fur SpaniiuiigsriRkorrosion bekannt s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The research was focused on the structure, properties, formation process and external factors of corrosion products in saturated H2S systems. [3][4][5][6] Ding et al investigated the behavior of corrosion and SCC of austenitic stainless steels in high H2S-CO2-Clenvironments. [7] Their results showed that high H2S-CO2 pressure can accelerate anodic dissolution process, deteriorate passive films, and aggravate SCC sensitivity.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…The research was focused on the structure, properties, formation process and external factors of corrosion products in saturated H2S systems. [3][4][5][6] Ding et al investigated the behavior of corrosion and SCC of austenitic stainless steels in high H2S-CO2-Clenvironments. [7] Their results showed that high H2S-CO2 pressure can accelerate anodic dissolution process, deteriorate passive films, and aggravate SCC sensitivity.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%